Word Recognition and Reading Skills to Improve Reading Comprehension - Mayra Yadira Chamba; Maria Rossana Ramirez-Avila (Universitas Muhammadiyah Yogyakarta, 2021)
This research aimed at showing the influence of word recognition, and using skimming and scanning skills to improve reading comprehension. Participants were a group of 15 students whose ages ranged from 14 to 16. They had problems in reading comprehension and vocabulary. This action research was conducted at a private language institute. The instruments to collect data were pre- and post-surveys, pre- post-tests, learning logs, skimming and scanning forms, and an interview. They provided quantitative and qualitative information. Results showed that there was a statistically significant improvement in parts of speech knowledge from the pre- to the post-test. The result was an average improvement of 28.2% in student performance. Cohen’s d was calculated with a result of 1.09 which means there is impact in learning. There was also a steady improvement in skimming and scanning which was exemplified by the ability to correctly complete a form after reading texts. Lastly, students’ perspectives were positive to this innovation. Therefore, it is advisable to apply the same innovation with other learners in order to compare results of improvement of reading comprehension and overall proficiency.